Effects of intensive fish-farming and domestic wastewater on the periphytic algal community in a tropical coastal lagoon (Juara, Brazil) - doi: 10.4025/actascibiolsci.v35i3.17094 - Almeida, Stéfano Zorzal de; Fernandes, Valéria de Oliveira (Acta Scientiarum. Biological Sciences, 2013)
This study aimed at evaluating the effects of the intensive fish-farming and the domestic wastewater on the structure of the phycoperiphyton community. Three experimental supports containing artificial substrate were assembled in two sampling sites: IF – region with intensive fish-farming and DW – near the domestic wastewater discharge. Samplings were carried out after the 21st, 26th and 31st day of colonization. The abiotic variables evaluated were: transparency, electrical conductivity, pH, turbidity, total suspended solids, alkalinity, dissolved oxygen, water temperature and nutrients. Phycoperiphyton was examined with regard to density, richness, abundance, dominance, diversity and eveness. Nutrients (total nitrogen, nitrate, ammonia nitrogen, orthophosphate and silicate) were different among the sampling sites. Although the total density, richness, diversity and evenness of phycoperiphyton were not affected by the different impacts, the density by class had differences between the sampling sites, with Bacillariophyceae presenting higher density at IF and Cyanophyceae and Coscinodiscophyceae at DW. Four taxa have been associated with the impact by domestic wastewater, and four, to the intensive fish-farming. The density by class of phycoperiphyton was the best attribute to evaluate the effects of human activity.